2021
DOI: 10.1111/hiv.13127
|View full text |Cite
|
Sign up to set email alerts
|

Risk of severe clinical events after sustained virological response following direct‐acting antiviral therapy in HIV and hepatitis C virus coinfected participants

Abstract: Objectives Sustained virological response (SVR) decreases the risk of hepatitis C virus (HCV)‐related events. Nevertheless, a substantial risk of events persists. We estimated incidences and identified factors associated with severe clinical events after SVR following treatment with a direct‐acting antiviral (DAA) in HIV/HCV‐coinfected patients. Methods Participants from the ANRS CO13 HEPAVIH were included if they reached SVR. Incidence rates of overall mortality, liver‐related events, AIDS‐defining events, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The finding that baseline albumin levels are associated with short-term improvement in liver fibrosis is similar to that of a previous report [30] , in which the authors observed an association between albumin levels and improvement in liver function among patients with cirrhosis. Moreover, another study utilizing ultrastructural observation to assess liver function suggested that elevated levels of cholinesterase and GGT might indicate severe liver fibrosis [31] . Notably, we also found a correlation between GGT levels and long-term improvement in liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that baseline albumin levels are associated with short-term improvement in liver fibrosis is similar to that of a previous report [30] , in which the authors observed an association between albumin levels and improvement in liver function among patients with cirrhosis. Moreover, another study utilizing ultrastructural observation to assess liver function suggested that elevated levels of cholinesterase and GGT might indicate severe liver fibrosis [31] . Notably, we also found a correlation between GGT levels and long-term improvement in liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%